Effects of age and maturation on lower extremity range of motion in male youth soccer players - Robles-Palazón, F. J.; Ayala, F.; Cejudo, A.; De Ste Croix, M.; Sainz de Baranda, P.; Santonja, F. (The Journal of Strength and Conditioning Research, 2022)
Restricted joint range of motion (ROM) has been considered as a primary risk factor for some sport-related injuries. Consequently, preparticipation assessment of lower extremity joints ROM could help identify youth soccer players at high risk of injury and to aid in the design of tailored age and maturational specific training interventions. The purpose of this study was to analyze and compare the influence of chronological age and maturational stage on several lower extremity ROM measures, as well as to describe the lower extremity ROM profile using a comprehensive approach in youth soccer players. A total of 286 male youth soccer players' ROM were assessed including passive hip (extension [PHE], adduction with hip flexed 90° [PHADHF90°], flexion with knee flexed [PHFKF] and extended [PHFKE], abduction with hip neutral [PHABD] and flexed 90° [PHABDHF90°], external [PHER] and internal [PHIR] rotation), knee (flexion [PKF]) and ankle (dorsiflexion with knee flexed [ADFKF] and extended [ADFKE]) ROMs. Between-group differences were analyzed using a one-way analysis of variance (ANOVA) and magnitude-based decisions. The results only report statistically significant (p < 0.05; d > 0.5) and clinically relevant differences (>8°) for the PKF ROM between U12 vs. U19, and Pre-PHV vs. Post-PHV groups. Furthermore, approximately 40, 35, and 20% of players displayed restrictions in their PHFKE, PKF, and ADFKF ROM values, respectively. These findings emphasize the necessity of prescribing (across all age groups and periods of growth and maturation) compensatory measures in daily soccer training, and these exercises should be equally applied to both limbs with the aim of improving PHFKE, PKF and ADFKF ROM values.